The Effect of Surface Roughness on Thermohydrodynamic Performance in Misaligned Journal Bearings - Abass, Basim Ajeel; K., Mustafa Mohammed (Al-Khwarizmi Engineering Journal, 2010)
In this work an approach has been developed to investigate the influence of surface roughness on thermohydrodynamic performance in aligned and misaligned journal bearings by considering an average flow model and deriving the shear flow factor for various roughness configurations, similar to the pressure flow factor. An average Reynolds equation for rough surfaces is defined in term of pressure and shear flow factors, which can be obtained by numerical flow simulation, though the use of measured or numerically generated rough surfaces. Reynolds, heat conduction and energy equations are solved simultaneously by using a suitable numerical technique (Finite Difference Method) to obtain the pressure and temperature distribution through the oil film thickness of the journal bearing. These equations are obtained for isotropic surfaces and for surfaces with directional patterns. The flow factors for these surfaces are expressed as empirical relations in term of normalized oil film thickness (h/σ) and surface characteristic (γ) defined as the ratio of x and z correlation lengths . The results of this approach showed increase in load carrying capacity and maximum pressure and decrease in maximum temperature in the case of stationary surface roughness (rough bearing and smooth journal) with transverse pattern. The results obtained through this work have been compared with that published by other works and found to be in a good agreement.